Biodegradable open-porous scaffolds made of sintered magnesium W4 and WZ21 short fibres show biocompatibility in vitro and in long-term in vivo evaluation. (August 2022) - Bobe, Katharina; Willbold, Elmar; Haupt, Maike; Reebmann, Mattias; Morgenthal, Ingrid; Andersen, Olaf; Studnitzky, Thomas; Nellesen, Jens; Tillmann, Wolfgang; Vogt, Carla; Vano-Herrera, Kelim; Witte, Frank
Abstract: Open-porous scaffolds made of W4 and WZ21 fibres were evaluated to analyse their potential as an implant material. WZ21 scaffolds without any surface modification or coating, showed promising mechanical properties which were comparable to the W4 scaffolds tested in previous studies. Eudiometric testing results were dependent on the experimental setup, with corrosion rates differing by a factor of 3. Cytotoxicity testing of WZ21 showed sufficient cytocompatibility. The corrosion behavior of the WZ21 scaffolds in different cell culture media are indicating a selective dealloying of elements from the magnesium scaffold by different solutions. Long term in-vivo studies were using 24 W4 scaffolds and 12 WZ21 scaffolds, both implanted in rabbit femoral condyles. The condyles and important inner organs were explanted after 6, 12 and 24 weeks and analyzed. The in-vivo corrosion rate of the WZ21 scaffolds calculated by microCT-based volume loss was up to 49 times slower than the in-vitro corrosion rate based on weight loss. Intramembranous bone formation within the scaffolds of both alloys was revealed, however a low corrosion rate and formation of gas cavities at initial time points were also detected. No systemic or local toxicity could be observed. Investigations by μ-XRF did not reveal accumulation of yttrium in the neighboring tissue. In summary, the magnesium scaffold´s performance is biocompatible, but would benefit from a surface modification, such as a coating to obtain lower the initial corrosion rates, and hereby establish a promising open-porous implant material for load-bearing applications. Statement of significance: Magnesium is an ideal temporary implant material for non-load bearing applications like bigger bone defects, since it degrades in the body over time. Here we developed and tested in vitro and in a rabbit model in vivo degradable open porous scaffolds made of sintered magnesium W4 and WZ21 short fibres. These scaffolds allow the ingrowth of cells and blood vessels to promote bone healing and regeneration. Both fibre types showed in vitro sufficient cytocompatibility and proliferation rates and in vivo, no systemic toxicity could be detected. At the implantation site, intramembranous bone formation accompanied by ingrowth of supplying blood vessels within the scaffolds of both alloys could be detected. Graphical abstract: Image, graphical abstract